Birth control pill trials in Sri Lanka: the history and politics of women’s reproductive health (1950-1980) - Thoradeniya, Darshi (Social history of medicine, 2020)
This paper draws on the history of the birth control pill in Sri Lanka to illustrate how the broader global discourse of population control was played out in the Sri Lankan national context. Utilising a cross reading of research reports and correspondence between local and international family planning pioneers such as Gregory Pincus, Clarence Gamble, John Rock and Siva Chinnatamby, I show how Sri Lanka became a laboratory for global pill trials. This prompted a discussion on contraception that revolved around morality and ethnicity resulting in the pill being labelled vanda pethi (sterility pills) by the 1960s. Vanda pethi became Mithuri (female friend) through the IPPF funded programme on social marketing of contraceptives in 1974. Analysing this programme I show how the women’s bodies of Sri Lanka became the ground on which ethnic politics at the local level, and liberal market forces at the global level, were played out through the introduction of the pill.
Advance access published 26 October 2018
Gesehen am 18.05.2021